2020
DOI: 10.1109/tsg.2019.2950875
|View full text |Cite
|
Sign up to set email alerts
|

Model-Free Optimal Voltage Phasor Regulation in Unbalanced Distribution Systems

Abstract: The proliferation of phasor measurement units (PMUs) into electric power distribution grids presents new opportunities for utility operators to manage distribution systems more effectively. One potential application of PMU measurements is to facilitate distribution grid re-configuration. Given the increasing amount of Distributed Energy Resource (DER) penetration into distribution grids, in this work we formulate an Optimal Power Flow (OPF) approach that manages DER power injections to minimize the voltage pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Explicit ZIP coefficients for commercial, residential and industrial loads have been proposed for conservation of voltage reduction (CVR) studies in unbalanced distribution systems [19], though this customer variety is only found in MV systems. A common ZIP load structure has even been employed in studies following model-free approaches of distribution system optimization, see [20] for example (phasor regulation strategy), with the work assuming the simplest form of an unbalanced system. Comparisons between different load models have been performed, though these are either on a purely technical level, i.e., behavior of single, standalone load [21], or comparisons between the standard ZIP model and different approximations of it [22].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Explicit ZIP coefficients for commercial, residential and industrial loads have been proposed for conservation of voltage reduction (CVR) studies in unbalanced distribution systems [19], though this customer variety is only found in MV systems. A common ZIP load structure has even been employed in studies following model-free approaches of distribution system optimization, see [20] for example (phasor regulation strategy), with the work assuming the simplest form of an unbalanced system. Comparisons between different load models have been performed, though these are either on a purely technical level, i.e., behavior of single, standalone load [21], or comparisons between the standard ZIP model and different approximations of it [22].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…T hese two porosity sets f or a closedloop behaviour by previous scalars p i , p j along z x(t) = x i=1,2.. (22) x(t), y(t) can be obtain by equations (23), (24) respectively x…”
Section: Soft Fuzzy Sets With System Statementioning
confidence: 99%
“…Our extended project team has developed and tested multiple L-PBC algorithms, including proportional-integral (PI) control [28], Linear Quadratic Phasor Control (LQPC), extremum-seeking (ES) control [31], and Retrospective Cost Adaptive Control (RCAC) [32]. The details of the controller design are not central to the PBC paradigm.…”
Section: Local Pbcmentioning
confidence: 99%